2018
DOI: 10.1186/s40729-017-0113-3
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a porcine collagen matrix in keratinized tissue augmentation: a 5-year follow-up study

Abstract: BackgroundWhen keratinized tissue width around dental implants is poorly represented, the clinician could resort to autogenous soft tissue grafting. Autogenous soft tissue grafting procedures are usually associated with a certain degree of morbidity. Collagen matrices could be used as an alternative to reduce morbidity and intra-operatory times. The aim of this study was to assess the efficacy of a xenogeneic collagen matrix as a substitute for soft tissue grafting around dental implants.MethodsFifteen consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…The overall integration of the graft with the surrounding tissues was favorable in terms of color matching, texture, and contour blending. This confirms previously published reports of using BCM around natural teeth and dental implants …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The overall integration of the graft with the surrounding tissues was favorable in terms of color matching, texture, and contour blending. This confirms previously published reports of using BCM around natural teeth and dental implants …”
Section: Discussionsupporting
confidence: 93%
“…The main concern in using BCM is the amount of postoperative volume shrinkage. Maiorana et al . observed tissue shrinkage at a percentage of 37% at 6 months, 48% after 1 year, and 59% after 5 years, while Sanz et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[26][27][28] XCM was also demonstrated to be effective in the long term, with stable esthetics. 29 In contrast to this, Cairo et al 30 observed a more effective increase in soft-tissue thickness with the application of CTG than with XCM. In terms of recession reduction using a coronally advanced flap with either a CTG or XCM, both achieved comparable and stable results.…”
Section: Introductionmentioning
confidence: 94%
“…In several studies, applying a XCM to increase soft‐tissue thickness was found to be as effective as a CTG . XCM was also demonstrated to be effective in the long term, with stable esthetics . In contrast to this, Cairo et al .…”
Section: Introductionmentioning
confidence: 99%